2021
DOI: 10.3390/ijms22126186
|View full text |Cite
|
Sign up to set email alerts
|

New Insights of SF1 Neurons in Hypothalamic Regulation of Obesity and Diabetes

Abstract: Despite the substantial role played by the hypothalamus in the regulation of energy balance and glucose homeostasis, the exact mechanisms and neuronal circuits underlying this regulation remain poorly understood. In the last 15 years, investigations using transgenic models, optogenetic, and chemogenetic approaches have revealed that SF1 neurons in the ventromedial hypothalamus are a specific lead in the brain’s ability to sense glucose levels and conduct insulin and leptin signaling in energy expenditure and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 91 publications
(172 reference statements)
1
13
0
Order By: Relevance
“…They reported that hypothalamic POMC neurons were modulated by sex hormones, as estradiol in post-synaptic POMC impaired CB1 receptor signaling at glutamatergic pre-synaptic terminals led to a reduction in food intake, whereas testosterone had the opposite effect [ 111 , 112 ]. More recently, the same authors reported that SF1 neurons of the VMH furnish sexually differentiated endocannabinoid- and diet-sensitive glutamatergic inputs to ARC/POMC neurons that would suggest a basis for sex differences in cannabinoid regulation for energy homeostasis [ 113 , 114 ]. For electrophysiological recordings in hypothalamic slices from intact and castrated guinea pigs, and in vitro optogenetic experiments in intact male and ovariectomized female SF1-Cre mice, the following specific findings were reported: (1) testosterone increased endocannabinoid tone at SF1/POMC synapses by increasing intracellular calcium; (2) endocannabinoid-mediated retrograde inhibition of glutamatergic input at SF1/POMC synapses was sexually differentiated and negatively regulated by estradiol; and (3) HFD feeding had a substantial impact on sex differences in endocannabinoid-induced regulation of energy homeostasis.…”
Section: Hypothalamic Endocannabinoid Signaling In Obesitymentioning
confidence: 99%
“…They reported that hypothalamic POMC neurons were modulated by sex hormones, as estradiol in post-synaptic POMC impaired CB1 receptor signaling at glutamatergic pre-synaptic terminals led to a reduction in food intake, whereas testosterone had the opposite effect [ 111 , 112 ]. More recently, the same authors reported that SF1 neurons of the VMH furnish sexually differentiated endocannabinoid- and diet-sensitive glutamatergic inputs to ARC/POMC neurons that would suggest a basis for sex differences in cannabinoid regulation for energy homeostasis [ 113 , 114 ]. For electrophysiological recordings in hypothalamic slices from intact and castrated guinea pigs, and in vitro optogenetic experiments in intact male and ovariectomized female SF1-Cre mice, the following specific findings were reported: (1) testosterone increased endocannabinoid tone at SF1/POMC synapses by increasing intracellular calcium; (2) endocannabinoid-mediated retrograde inhibition of glutamatergic input at SF1/POMC synapses was sexually differentiated and negatively regulated by estradiol; and (3) HFD feeding had a substantial impact on sex differences in endocannabinoid-induced regulation of energy homeostasis.…”
Section: Hypothalamic Endocannabinoid Signaling In Obesitymentioning
confidence: 99%
“…Recently, Fosch and colleagues have summarized key molecules or targets implicated into glucose homeostasis and/or energy balance in the VMH based on SF1-Cre transgenic mice (for the review see Ref. [ 129 ]). In addition, most recent studies suggested that Rap1 and prostaglandin in the VMH have also been implicated into glucose homeostasis [ 123 , 128 ].…”
Section: Heterogeneity Of Vmh Neurons In Glucose Regulationmentioning
confidence: 99%
“…Evidence has also highlighted the participation of non-neuronal populations (i.e., microglia and astrocytes), and even the interesting cross-talk between these types of brain cells, whose disruption leads to insulin resistance and obesity. In this Special Issue, we report on the most recent insights into the hypothalamic circuitries and pathways involving neurons [3][4][5][6][7], astrocytes [8,9], and microglia [10,11] in obesity development and associated complications. The emerging contribution of astrocyte-neuron [9] and microglia-neuron cross-talks [12] in the hypothalamus and the contribution of microbiota and the gut-brain axis controlling food intake and energy homeostasis [13] are also presented in this Special Issue (Figure 1).…”
mentioning
confidence: 99%
“…For instance, lacking SIRT1 or SIRT6 in POMC neurons affects energy expenditure and adiposity; however, SIRT1 in AgRP neurons specifically affects eating behavior, and in oxytocin neurons in the PVN controls diet preference. In addition to sirtuins, Fosch et al [4] provide new insights into other targets in SF1 neurons of the ventromedial hypothalamus that play a critical role not only in body weight control and adiposity, but also in glucose tolerance and insulin and leptin sensitivity, with minimal effects on food intake and differential actions between male and female mice. The authors also report how nutrient sensors such as AMPK and SIRT1, glutamatergic transmission, synaptic receptors, and mediators of autophagy in SF1 neurons are promising therapeutic targets against obesity and diabetes, reinforcing the "central role" of the hypothalamus in the control of peripheral metabolism beyond the regulation of feeding behavior [4].…”
mentioning
confidence: 99%
See 1 more Smart Citation